The Impact of Interdisciplinary Teacher Teaming on the Academic Success of High School - Kealen, Adam (Southwest Baptist University, 2017)
The landscape of education is changing. Students in today’s society are living in a world where poverty is increasing, broken homes are becoming more common, and safety on their streets is coming into question. With these changing times, is the institution of public education changing? This study focused on the need for schools to become developmentally responsive to the changing needs of students through the personalization of the learning environment, specifically that of the high school setting. This research specifically focused on the use of an interdisciplinary team of teachers as a strategy to monitor the academic success of freshman-aged students in an effort to combat the traditional issues students face as they transition from middle school to high school. Whereas current research and literature does exist in identifying this problem and providing possible solutions, the use of this specific strategy in light of personalizing the environment to meet the developmental needs of students is sparse. To measure the effectiveness of this strategy, the 4-year graduation rates of identified schools were used in a causal-comparative quantitative study. Schools in the states of Missouri and Kansas were electronically surveyed both to identify schools that used this strategy as well as assess their perceptions on how this strategy has impacted the teacher-student relationships within their buildings. The study revealed a statistical significance did exist in schools that utilized this strategy and their 4-year graduation rates as compared to demographically paired schools that did not. In addition, a strong significance was found between the perceived teacher-student relationships and schools that employed this strategy as compared to schools that did not.